Foraging behaviour of honeybees in hybrid seed production of sunflower (Helianthus annuus)* - CHAKRABARTY, S K; SHARMA, S P (The Indian Journal of Agricultural Sciences, 2011)
Field experiments were conducted to study honeybee behaviour in sunflower hybrid seed production. Frequency of honeybees visit and their duration of foraging was different in two parental lines and in the morning and evening hours. More honeybees were recorded in the morning hours on the male parent plants as compared to those in the female parent plants. Dry nectar sugar production was more in evening hours in florets of female plants and in morning hours in the male. A positive relationship was observed between nectar production and foraging behaviour of honeybee. In hybrid seed production plot honeybees abundance and foraging duration were significantly higher in female lines adjacent to male lines compared to rows away from male line. A difference in seed yield obtained in different rows in female line has been discussed in the light of pollination by honeybees.